Examining the Concept of Principles in Curriculum Development - HR, Sabriadi; Wakia, Nurul; Aziz, Muh Bachtiar (DIDAKTIKA, 2024)
This research is based on a study of the principles of curriculum development which includes an understanding of the meaning of the curriculum in the teaching context. Curriculum is a general plan that summarizes the learning objectives, content, teaching methods, and assessments used in an educational program. Curriculum development is a complex process and involves various principles that must be taken into account. This research aims to find out and examine the principles of curriculum development. To obtain data from this problem, the author uses a qualitative descriptive method in the form of a literature review, thus proving a scientific study that can be researched and developed further. This research data collection technique was carried out by collecting various reference sources or literature that were considered appropriate, both in the form of soft and written text such as scientific articles, articles, textbooks, etc. The results of the data obtained by the author suggest that there are several principles of curriculum development that are often explored in research, including relevance, continuity, flexibility, effectiveness, practicality and others. By referring to the principles of curriculum development, curriculum development can work consistently, with direction, and with accountable results. Apart from that, the differences in principles in the curriculum and its development are marked by the fact that the curriculum itself is a field of study. Examining the principles of curriculum development can help increase our understanding of how to design an effective curriculum and respond to changing times. By understanding these principles, policy makers developing curricula can provide relevant and meaningful learning experiences for students.